Corporate Social Responsibility and Strategic Management of Business Development in Small and Medium-Sized Enterprises - Stoyanov, Philip (Dr. Viktor Koval, 2025)
Introduction. Corporate social responsibility has recently evolved from a concept into a comprehensive, meaningful, and in-depth policy, with the help of business organisations becoming a responsible element of society. Although it enjoys increased interest at the global and European levels, corporate social responsibility (CSR) is still not a widespread practice in the policies of Bulgarian micro, small, and medium-sized enterprises. Aim and tasks. The aim is to identify the main specific features of the implementation of CSR in Bulgarian conditions, as well as the attitudes of management towards a stronger advocacy of various CSR initiatives, both internal and external to the company. Results. This study is based on data from a survey conducted among representatives of Bulgarian micro, small, and medium-sized enterprises operating in different sectors of the economy. The analysis of the data from a survey of 205 companies shows that CSR is perceived mainly as a tool for improving the image and meeting the expectations of customers and partners. Taking care of employees is the most common practice (45%), while initiatives aimed at the community and environment remains more limited and often episodic. Most companies do not have a formal CSR policy (41.5%), with top management leading the way in introducing CSR initiatives. It was found that attitudes towards CSR were positive. However, a lack of institutional incentives and limited resources hinders the more systematic integration of socially responsible practices. Top management (51%) initiates CSR in Bulgarian companies, making it more fragmented than strategically integrated. Most respondents (72%) see CSR as a way to improve image, but 55% consider such investments difficult to justify. The main barrier to development is the lack of government support. This pattern, where 51% of initiatives come from managers, shows that CSR is an image rather than a strategic initiative. Although companies value reputational benefits (72% for image and 67% for expected customers), only 16% have specialised CSR departments. The main obstacle remains the lack of adequate government policy, with more than 50% of respondents agreeing. Conclusions. CSR in Bulgaria is perceived mainly as a means of building a reputation, but its practical implementation remains limited by resource and institutional factors. A trend towards strengthening internal practices and readiness for broader integration of external initiatives under the pressure of the international market and regulation. In this sense, CSR in Bulgarian enterprises can be defined as a practice in the process of institutionalisation, the development of which requires both more active management commitment and the creation of a stimulating environment at the national level.